Diethylphosphonate‐containing benzoxazine compound as a thermally latent catalyst and a reactive property modifier for polybenzoxazine‐based resins. Issue 16 (6th June 2013) - Lin, Liang‐Kai; Wu, Chuang‐Shao; Su, Wen‐Chiung; Liu, Ying‐Ling
ABSTRACT: A diethylphosphonate‐containing benzoxazine compound (DEP‐Bz) to be used as a multi‐functional reaction agent for preparation of high performance polybenzoxazine thermosetting resins has been reported. The chemical structure of DEP‐Bz has been characterized with FTIR, 1 H NMR, and elemental analysis. The phosphonate groups of DEP‐Bz could convert into phosphonic acid groups which could catalyze the ring‐opening addition reaction of benzoxazines, to demonstrate the thermally latent catalytic effect of DEP‐Bz on the polymerization of benzoxazine compounds. Moreover, DEP‐Bz could also serve as a reactive‐type modifier for polybenzoxazines and other thermosets. DEP‐Bz modified polybenzoxazine resins have shown relatively low reaction temperature (about 190 °C), high mechanical strength with a storage modulus of about 3.0 GPa, and high flame retardancy with a limit oxygen index of about 32. © 2013 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2013, 51, 3523–3530 Abstract : A diethylphosphonate‐containing benzoxazine compound has been prepared to be used as a multi‐functional reaction agent for preparation of high‐performance polybenzoxazine thermosetting resins. The phosphonate group shows the thermally latent catalytic effect and flame retardation, and the benzoxazine group causes the compound to be a reactive‐type reagent.